PENGARUH JENIS DAN KONSENTRASI ASAM TERHADAP NILAI DEXTROSE EQUIVALENT PADA HIDROLISIS PATI UBI TALAS (Colocasia esculenta L. Schoot) - Cahyani Putri, Nopia; Hartiati, Amna; Admadi, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 3 (2016): September, 2016)
This research aims to 1)  find out the effect of acid concentration and  interaction of the  Dextrose equivalence  (DE) value  hydrolysis  starch, 2) to find out the type and concentration of acid that produces  highest DE  value starch hydrolysis results.  This study used a factorial Randomized Block Design with factorial pattern. The first factor is the type of acid solvent consisting of  3  levels hydrolysis of starch with HNO 3 3M, hydrolysis of starch with  H2SO4 3M,  hydrolysis of starch HCl 3M and the second factor is :  5%, 6%, 7%.  Each treatment was divided into two  according  by the time of implementation. Variables observed that reducing sugar, total sugar, and  Dextrose equivalence (DE). Determining the best treatment  done with the analysis of the DE value of taro starch. Treatment acids very significant effect on the value of  hydrolyzed  taro  starch DE while the acid concentration and interaction treatment did not significantly affect  on  the value of taro starch DE hydrolyzed. Starch hydrolysis involves the kinds of    3M  sulfuric acid at a concentration of 7% is the best treatment to the value of  Dextrose Equivalence (DE) highest, the number of 37,93%. Keywords: hydrolysis, acid, DE, starch, taro
Keywords: 113